Bibiliometric Analysis using Vosviewer with Publish or Perish of Fiber As A Soilless Planting Medium - Nuryantini, Ade Yeti (Bumi Publikasi Nusantara, 2024)
The use of soilless planting media is currently increasingly in demand because land for agriculture is decreasing as a result of it being used for residential and industrial construction. One of the preferred planting media options is fiber, both natural and synthetic. This research aims to analyze publication trends regarding the use of fiber as a soilless planting medium, using bibliometric methods and mapping with the VOSviewer application. Publication data was taken from Google Scholar between 2019 and 2024, and a total of 942 documents were found during that period. Publication trends regarding the use of fiber as a soil-free planting medium fluctuate, increasing and decreasing every year. The number of documents in 2019 decreased, although not too significantly. But from 2019 to 2023 there was a soaring increase. At the beginning of 2024, interest in research on the use of fiber as a soil-free growing medium will increase rapidly, as shown by the publication of 52 publications at the beginning of the year. The results of three types of mapping show that research on fiber continues to develop along with the various types of fiber used as planting media. Therefore, further research regarding the development of fiber as a soilless growing medium is still relevant and very necessary and could be a driving force for further research to find innovations in this field.